The biology of psychological disorders - Linden, David (Houndsmills, Basingstoke, Hampshire New York, NY Palgrave Macmillan, 2012)
"Covering a broad range of psychological disorders, their biological underpinnings, and the latest principles of pharmacological treatment, The Biology of Psychological Disorders is essential reading for students specializing in biological psychology, or seeking to contextualize their studies of cognitive and clinical neuroscience"--
Introduction -- pt. I. Basic neuroscience and research methods -- 1. Neuroanatomy -- Neuron -- Glia cells -- The nervous system -- 2. Neurophysiology and basic neurochemistry -- Neurons -- NTs -- 3. Neuroendocrinology -- Hormones -- Hypothalamic-pituitary system -- Tuberoinfundibular dopamine pathway -- HPA axis -- Neuroendocrine and immune systems interact -- Sex hormones -- 4. Genetics -- Molecular genetics -- Cellular genetics -- Genetic variation and patterns of inheritance -- 5. Animal models of human behavior and mental disorders -- Learning theory -- Anxiety disorders -- Chronic stress -- Animal models of schizophrenia use putative endophenotypes -- Animal models have also been designed for ADHD, addiction and most other mental disorders -- pt. II. Psychopharmacology -- 6. General principles of psychopharmacology -- Ligand-receptor complexes -- Action of neurotransmitters -- Pharmacokinetics describes the fate of drugs in the body -- Overdosing, toxicity and antidotes -- Old age and pregnancy -- Prescribing controlled drugs -- Adverse effects -- 7. Neurotransmitter receptors and postsynaptic signaling pathways -- Ionotropic NT receptors -- Voltage-gated channels -- Metabotropic receptors -- Signaling cascades in the postsynaptic cell -- 8. Physical therapies -- Sleep deprivation and light therapy aim to rebalance circadian rhythms in depression -- Electroconvulsive therapy induces brief generalized seizures -- Vagus nerve stimulation -- Surgery and deep brain stimulation directly interfere with putative pathophysiological networks -- Neurofeedback : modulating brain activity -- 9. Biological effects of psychotherapy -- Psychotherapy changes the brain -- Behavioral therapy and medication for anxiety disorders : similar neural effects -- Brain effects pf cognitive behavioral therapy for depression and antidepressants may differ -- Specific pharmacotherapy : add-on to psychotherapy -- Placebos -- pt. III. Clinical disorders -- 10. Schizophrenia and related disorders -- History -- Clinical syndrome and natural history -- Epidemiology -- Genetics -- Brain structure and function -- Neurochemistry -- Animal models -- Treatment -- 11. Depression -- History -- Clinical syndrome and natural history -- Epidemiology -- Genetics -- Brain structure and function -- Neurochemistry -- Animal models -- Treatment -- 12. Mania and bipolar disease -- Clinical features -- Epidemiology and natural history -- Genetics -- Brain structure and function -- Neurochemistry and mechanism of drug action -- Animal models -- Treatment with mood stabilizers -- 13. Anxiety disorders -- History -- Clinical syndromes -- Epidemiology -- Genetics -- Brain structure -- Brain function -- Neurochemistry and pharmacological treatment -- Animal and experimental models -- 14. Biology of personality disorders -- Definition, clinical presentation and epidemiology -- Heritability -- Models of personality -- Categorical vs. dimensional models of personality disorders -- Biology of personality disorders -- Animal models -- 15. Biology of substance-related disorders -- Clinical classification -- Alcohol use disorders -- Stimulant abuse and dependence -- Opioid-related disorders -- Abuse of other substances -- 16. Eating disorders and disorders of impulse control -- 17. Mental disorders of childhood and adolescence -- Attention deficit/hyperactivity disorder -- Autism (Autistic disorder and Asperger's disorder) -- Conduct disorder -- 18. Biology of sexual and gender identity disorders -- Definition, clinical aspects and epidemiology -- Neuropsychiatry of altered sexual behavior -- Pharmacology and treatment of abnormal sexual behavior -- Gender preference -- Neurobiological differences between genders and gender identity -- 19. Biology of sleep disorders -- Definition, clinical aspects and epidemiology -- Parasomnias -- Treatment of sleep disorders -- 20. Aging and dementia -- Psychology of aging -- Neurobiology of aging -- Definition and subtypes of dementia -- Alzheimer's disease -- Frontotemporal dementia -- Parkinson plus syndromes -- Prion disease -- Lewy Body dementia -- Vascular dementia -- Normal pressure hydrocephalus -- Dementia pugilistica ("boxer's dementia") -- Alpha synuclein : common feature in neuropathology of dementias -- Animal models -- 21. Neuropsychiatry -- Syndromes -- Pathologies -- Treatment -- Afterword : the future of biological psychiatry -- Glossary : biological and neuroanatomical terms and methods.
Keywords: Mental illness; Neurophysiology; Mental illness; Mental Disorders; Mental Disorders; Neurosciences; Psychotropic Drugs; Mental illness; Mental illness; Neurophysiology